Imagining transformative biodiversity futures - Wyborn, C; Davila, F; Pereira, L; Lim, M; Alvarez, I; Henderson, G; Luers, A; Martinez Harms, MJ; Maze, K; Montana, J; Ryan, M; Sandbrook, C; et al. (Springer Science and Business Media LLC, 2020)
The world has changed. Posited to be a ‘super year’ for biodiversity with various international meetings and the conclusion of the Convention on Biological Diversity’s ten-year Aichi Targets, 2020 will be remembered for very different reasons: catastrophic fires, the COVID-19 pandemic, floods, locust outbreaks, a drastic drop in oil prices and widespread food insecurity. These disruptions will exacerbate the already considerable gap between rich and poor, hitting marginalized groups — the impoverished, women, Indigenous communities and people of colour — much harder. Impacts on the environment have been mixed: carbon emissions may be down, but there are growing concerns that nature will be forgotten in the rush to rebuild devastated economies.
Keywords: 40 Engineering; 41 Environmental Sciences